Načrtovanje donosov pri mnogonamenskem gospodarjenju z gozdovi - Bončina, Andrej (Gozdarski vestnik, 2008)
Determined allowable cut and its execution have, together with social-economics conditions, significantly influenced the development of the forest stands in Slovenia. In the period 1947-2006 forest recourses in Slovenia have changed remarkably; without taking into consideration the pioneer forests which have appeared on abandoned agricultural land, average growing stock of Slovenian forest increased in the period 1947-2006 from 124 to 285 m3/ha. Additionally, the amount of medium and large size trees has increased significantly. Both the increase of growing stock and larger portionof large size diameter trees indicate efficiency and success of the regular forest management. At the same time, structural changes of forest resources indicate that more attention should be paid to issues concerning forest regeneration and maintaining of desired growing stock structure. According to the Forest Act, in the process of forest management planning allowable cut should be determined in accordance with current forest management objectives. The allowable cut determination is closely connected tothe forest development planning; the allowable cut is a result of quantification of decisions concerning further forest stand development, wheretwo approaches are combined - the detailed and the frame planning approach. In the article, procedures for allowable cut determination in the planning process are presented separately for even-aged and uneven-aged forestmanagement.
Keywords: gozdno gospodarstvo; posek; donos; gozdovi; načrtovanje; Slovenia; Slovenija